Antologi Metode Pendidikan Islam Berdasarkan Ayat-ayat Al-Quran - Fiqih Nur Laili; Abdul Rouf; Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2022)
The method is a set of ways, paths and techniques used by the teacher (educator) in the teaching and learning process so that students (students, students) achieve specific learning goals or competencies formulated in the curriculum, syllabus and subjects. Islamic Education is a conscious and planned effort to realize the learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation and state accordingly with the teachings of Islam for happiness to live in the world and the world. To give birth to qualified students, the right method is needed in providing learning material, as contained in several verses in the Al-Qur'an that explain the method of education. Among them are, the tamstsil method (parables), the qashashi method (stories or stories), the exemplary method, the ibrah and mau'izhah methods (interpreting and advice), the targhib and tarhib methods (Reward and Punishment).